Mcardle disease: New insights into its underlying molecular mechanisms - Llavero, Francisco (2019)
McArdle disease, also known as glycogen storage disease type V (GSDV), is characterized by exercise intolerance, the second wind phenomenon, and high serum creatine kinase activity. Here, we recapitulate PYGM mutations in the population responsible for this disease. Traditionally, McArdle disease has been considered a metabolic myopathy caused by the lack of expression of the muscle isoform of the glycogen phosphorylase (PYGM). However, recent findings challenge this view, since it has been shown that PYGM is present in other tissues than the skeletal muscle. We review the latest studies about the molecular mechanism involved in glycogen phosphorylase activity regulation. Further, we summarize the expression and functional significance of PYGM in other tissues than skeletal muscle both in health and McArdle disease. Furthermore, we examine the different animal models that have served as the knowledge base for better understanding of McArdle disease. Finally, we give an overview of the latest state-of-the-art clinical trials currently being carried out and present an updated view of the current therapies.